Strategi Guru Pendidikan Agama Hindu Dalam Menguatkan Etika Tri Kaya Parisudha Murid Kelas XI Di SMA (SLUA) Saraswati 1 Denpasar - Dewi Asih; I Nyoman Alit Supandi; Ida Ayu Gde Wulandari (Scientific Journal for Nation Building, 2026)
Hindu Religious Education plays an important role in shaping students’ ethics through the strengthening of religious values. One Hindu ethical teaching that is relevant to character formation is Tri Kaya Parisudha, which refers to good thoughts, good words, and good actions. However, school life still shows that some students have not fully reflected these values, such as using impolite language, lacking discipline, and showing low responsibility. This study aims to: (1) describe the strategies used by Hindu Religious Education teachers in strengthening Tri Kaya Parisudha ethics among grade XI students at SMA (SLUA) Saraswati 1 Denpasar, and (2) describe the obstacles faced and the efforts made by teachers in strengthening Tri Kaya Parisudha ethics. This study used a descriptive qualitative approach with a phenomenological perspective. Informants were selected using purposive sampling. Data were collected through observation, interviews, documentation, and literature study. The data were analyzed through data collection and preparation, coding and data grouping, theme identification, thematic narrative construction, and conclusion drawing and verification. The results of the study showed that the strategies used by Hindu Religious Education teachers in strengthening Tri Kaya Parisudha ethics were carried out through ethical strengthening planning, teacher role modeling in learning, habituation of ethical attitudes and behavior, reinforcement through advice, reflection, and value discussion, as well as the teacher’s role as an educator, guide, and ethical model. The obstacles included diverse student characteristics, low awareness among some students in maintaining ethics, impolite speaking habits, lack of parental supervision, and the influence of technology and peer environment. The efforts made by teachers included personal approaches, continuous advice and guidance, habituation of positive behavior, providing good examples, using interesting learning methods, and cooperating with the school and parents.